DA ESPECIFICIDADE DO ESTILO RETÓRICO SEGUNDO ARISTÓTELES - Francisco, Maria de Fátima Simões (Organon, 2012)
In this paper we intend to examine some of the suggestions regarding the style provided byAristotle in his Rhetoric, chapters III, 2-12, in order to enable, on the one hand, the understanding of thespecificity of such a style in Aristotle's conception and, on the other hand, analyze in what way thecharacteristics inherent to the rhetoric style are linked to the persuasive function of such speech.